Comparative investigation of composite-metal lap joints with mono-adhesive and thermoplastic-reinforced mixed adhesive at elevated temperatures - Erbayrak, Engin; Eker, Beril; Colak, Murat (TAYLOR & FRANCIS LTD, 2026)
This study primarily examines the strength of a single lap joint having a mixed adhesive overlap consisting of a single adhesive and its thermoplastic reinforced state under varying temperatures. In the single lap joint, Titanium-Boron reinforced A356 aluminum was employed as the metal adherend, while plain woven glass fiber-reinforced epoxy (GFRE) was employed as the composite adherend. In the application of the mixed adhesive overlap, the brittle adhesives were employed in the middle section of the lap joint, while the reinforcement of the thermoplastics was employed on the adhesives at both sides of the lap joint. The single lap joints were subjected to tensile tests at 1 mm/min loading rates under room temperature and 120 degrees C, which is the melting point of the copolyester. In the numerical analysis, the cohesive zone model was applied in order to define the adhesives; however, elastic isotropic and orthotropic material behaviors were employed for the metal and composite adherends, respectively. Eventually, it is determined that the strength of a mixed adhesive lap joint consisting of a single adhesive and its thermoplastic reinforced state is better than a lap joint made with the mono-adhesive alone. Although literature suggests that mixed adhesive overlaps can be formed using at least two different adhesives (one ductile and one brittle), this study demonstrated that a mixed adhesive zone can be created using a single adhesive and thermoplastic reinforcement.
Keywords: Mixed adhesive overlap; metal-composite single lap joint; temperature effect; mixed mode cohesive zone model; DYNAMIC COMPRESSION; FAILURE LOADS; BEHAVIOR; SIMULATION; INPLANE; Engineering; Materials Science; Mechanics